Association Between Clinical Decision Support System Use and Rural Quality Disparities in the Treatment of Pneumonia. Issue 2 (12th August 2013) - Mitchell, Jordan; Probst, Janice; Brock‐Martin, Amy; Bennett, Kevin; Glover, Saundra; Hardin, James
Abstract Purpose To determine whether there is an association between clinical decision support system (CDSS) use and quality disparities in pneumonia process indicators between rural and urban hospitals. Methods Data were used from the FY 2009 American Hospital Association electronic health record (EHR) adoption survey (3, 616 responding hospitals) to identify hospitals that used CDSS for clinical guidelines and reminders. This was linked to the 2009 Hospital Compare data set from the Centers for Medicare and Medicaid Services (3, 805 reporting hospitals). The merged data set contained 2, 405 hospitals: 1, 330 were noncritical in metropolitan ZIP Code Tabulation Areas (ZCTAs), 692 were noncritical in rural ZCTAs, and there were 383 critical access hospitals (CAHs; 359 in rural ZCTAs, 24 in urban ZCTAs). The dependent variable was a pneumonia composite quality score, composed of 6 pneumonia process indicators calculated for each hospital. Adjusted analysis controlled for a hospital's propensity to use CDSS. Findings While quality was lower in rural institutions, unadjusted pneumonia quality scores varied modestly, from 90.08% in CAHs to 93.38% in urban hospitals. Hospitals that used CDSS had higher unadjusted pneumonia process composite scores than their non‐CDSS counterparts. After controlling for CDSS use, the propensity for CDSS use, and hospital and community characteristics, hospitals in rural ZCTAs did not have significantly different process composite scores than their metropolitan counterparts. Conclusions CDSS was positively associated with quality of care for pneumonia. Adoption of EHRs with CDSS functionality in rural hospitals may serve to reduce quality gaps. Costs of EHR implementation may be a barrier to this process.